Theologising Brexit: a liberationist and postcolonial critique - Reddie, Anthony G. (Routledge new critical thinking in religion, theology, and biblical studies, 2019)
Behind the scenes -- Setting the scene -- Courting controversy: the anti Blackness problematic of mission Christianity -- Mind games: decolonizing mission Christianity -- Now you see me, now you don't: subjectivity, blackness and difference in practical theology in Brexit Britain -- Being the enemy within -- Responding to the challenge -- Reading the Bible and multiple religious belonging -- Education and learning to be different -- The critical challenge of the other -- Rastafari and Black theology -- Doing it our way: caribbean theology, contextualisation and cricket -- Telling the truth and shaming the devil.